Establishment of an Experimental Procedure for Preparing Trial Serum Samples for the Specific Serodiagnosis of Toxocara canis for External Quality Assessment Schemes - Quang Huy Vu; Diep Tuan Tran; Phu Manh Sieu Tran; Van Chuong Le; Thi Diem Phuc Huynh; Quang Sang Bui (Journal of Parasitology Research)
Background. External quality assessment (EQA) provides evidence of reliable, accurate, and precise results for customers using the diagnostic test for Toxocara canis. Objective. To establish a procedure for producing standard Toxocara canis serum samples for serodiagnostic testing in EQA. Methods. The collected serum samples to contain anti-Toxocara canis antibodies were screened by ELISA and confirmed by Western blotting. These samples were found to be negative for other helminth antibodies, anti-HIV-1 and -2 antibodies, anti-HCV antibodies, and antibodies to HBs antigen. The sera were divided, processed by both freeze-drying and freezing methods, and then stored. The stability and homogeneity of the samples were evaluated after 7 days, 1 month, 3 months, and 6 months. An F-test and a T-test were applied to evaluate their homogeneity and stability. Results. Among eleven samples positive by ELISA, ten of them were confirmed via Western blotting by positive reaction with 5 specific Toxocara canis bands. Two lots of trial standard sera containing specific anti-Toxocara canis antibodies were successfully produced. Lot DK had a concentration of 31.01±1.1 NovaTec Units (NTU), and Lot DL had a concentration of 27.18±0.9 NTU. After storage at -80°C, the samples prepared by the freeze-drying method were stable for at least 3 months, and the samples prepared by the freezing method were stable for 6 months (p>0.05). Samples produced by both methods were stable for 7 days at 30°C (p>0.05). Conclusion. Specific serodiagnosis samples of anti-Toxocara canis antibodies for EQA could be produced that possessed homogeneity and stability lasting for 3 months and 6 months by the freeze-drying and freezing methods, respectively. At 30°C, the samples produced by both methods were stable for 7 days, suitable for delivery to remote laboratories.